Analisis Kemampuan Metodologi Penelitian Mahasiswa Ditinjau Dari Kualitas Penulisan Skripsi - Gusman Lesmana (UMSU, 2023)
This research was conducted to see and analyze the ability of students to undergo the dynamics of writing scientific papers (thesis) as a final assignment to fulfill undergraduate graduation requirements at Muhammadiyah University, North Sumatra. The process of searching for data by carrying out integrated identification looks at the results of thesis produced by students from several study programs representing each faculty by looking at the specifications of the thesis that has been produced to see how fulfilled what is written in it by looking at existing research methodology indicators, such as writing procedures, templates, writing methods , clarity of research methods, data analysis to research conclusions. This is done by using survey analysis which will produce percentage data to see the increase in research methodology mastery that students have had for the past 2 years. The results of this study indicate that students are still confused about the use of research methods included in their thesis. The research data interval is Mastery 36.89%, Moderate 54.32%, Not yet Mastered 8.79%.